Os conceitos de abstrato e concreto na categoria mercadoria em O Capital de Marx - Fernandes, Viviane Bonfim (2010)
This work aims to explain why there is an inversion of the concrete and abstract concepts between the Classical Political Economy, specifically Adam Smith and David Ricardo, and Karl Marx, in the explanation of the theory of value, and why Marx goes further than the economists. It tries to clarify why, what the economists consider concrete to Marx, is no more than mere abstraction, showing that it is due to their different regards . This work debates on the explation way of them both the economists and Marx s -, on the subject of the value of goods. The differentiation between the two methods os explaining the thoughts gets clear the economist use the empriric method and Marx, the dialectic. It is this differentiation of the methods that invert the concepts. Marx uses the method proposed by Hegel as a way to expose the thought; as a consequence, it was necessary to a brief explanation on the hegelian dialectic method. At the end of the text, there is an explanation, step by step, of the relationship between Marx s exposition on the commodity category and the hegelian dialectic method. It is possible then to observe the similarities and differences between Marx and Hegel, and how Marx follow Hegel s orientations in his exposition, in relation of the exteriorization of the idea. In Hegel and Marx, the thought movement goes from the abstract to the concrete and is processed by progressive scales of concretization. Between the most abstract and the most concrete, there is a range of more or less abstract concepts linking the two extreme points; they are the mediations. The abstract has the concrete as a presupposition; the essence is the founder, and the shape is the founded, which means the material contents (concrete) make possible the criation of shape, appearance (abstract), which ends up denying its own essence (concrete) based on the perception that happens in a inverted way the common man believes that what he perceives, the appearance, is the essence; the contents are the reality, the concrete. Marx tries to demonstrate the process of knowing the reality, that goes from the abstract to the concrete. Dialectic is used as a mean of exposition and means the synthetic return of the analytical or the concrete reconstruction of the universal. Abstract and concret do not exist apart; they are part of a totality, of a unity. The abstraction method makes it possible to understand the categories of reality in a more detailed and deeper way, in order to mentally reconstruct the complex whole. In this way, the concrete happens due to the thought, it is the thought concrete, and the abstract is the empiric and deceptive perception of the capitalist society.